Aged Microplastics and Antibiotic Resistance Genes: A Review of Aging Effects on Their Interactions - Kuok Ho Daniel Tang; Ronghua Li (MDPI AG, 2024)
Background: Microplastic aging affects the dynamics of antibiotic resistance genes (ARGs) on microplastics, yet no review presents the effects of microplastic aging on the associated ARGs. Objectives: This review, therefore, aims to discuss the effects of different types of microplastic aging, as well as the other pollutants on or around microplastics and the chemicals leached from microplastics, on the associated ARGs. Results: It highlights that microplastic photoaging generally results in higher sorption of antibiotics and ARGs due to increased microplastic surface area and functional group changes. Photoaging produces reactive oxygen species, facilitating ARG transfer by increasing bacterial cell membrane permeability. Reactive oxygen species can interact with biofilms, suggesting combined effects of microplastic aging on ARGs. The effects of mechanical aging were deduced from studies showing larger microplastics anchoring more ARGs due to rough surfaces. Smaller microplastics from aging penetrate deeper and smaller places and transport ARGs to these places. High temperatures are likely to reduce biofilm mass and ARGs, but the variation of ARGs on microplastics subjected to thermal aging remains unknown due to limited studies. Biotic aging results in biofilm formation on microplastics, and biofilms, often with unique microbial structures, invariably enrich ARGs. Higher oxidative stress promotes ARG transfer in the biofilms due to higher cell membrane permeability. Other environmental pollutants, particularly heavy metals, antibacterial, chlorination by-products, and other functional genes, could increase microplastic-associated ARGs, as do microplastic additives like phthalates and bisphenols. Conclusions: This review provides insights into the environmental fate of co-existing microplastics and ARGs under the influences of aging. Further studies could examine the effects of mechanical and thermal MP aging on their interactions with ARGs.